KEMAMPUAN MEMBACA TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 16 PEKANBARU - Niken Nurhayati; Dudung Burhanudin; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research entitled the ability to read the exposition of the text of students of class VIII SMP Negeri 16 Pekanbaru. This study aims to describe the ability to read the exposition of the text of students of class VIII SMP Negeri 16 Pekanbaru, to describe whether there is a significant difference in the ability to read the expositional text of the students of grade VIII SMP Negeri 16 Pekanbaru between the sample groups and between the sexes. The type of this research is descriptive-quantitative. The population of this study amounted to 125 and 95 samples. The data of this study is the test results of students in the test of reading ability exposition of students of class VIII SMP Negeri 16 Pekanbaru. The test used is an objective test consisting of four alternative answers. The data were analyzed by quantitative descriptive method through t test to know the level of reading ability of expositional text of VIII students of SMP Negeri 16 Pekanbaru, one way anova test to know difference of reading ability of expositional text of Grade VIII students of SMP Negeri 16 Pekanbaru between sample group and two way anova test to know the difference in the ability to read the exposition text of the students of class VIII SMP Negeri 16 Pekanbaru between the sexes. The result of this research is the result of reading ability text test of the students' exposition of class VIII SMP Negeri 16 Pekanbaru is moderate with average valueKeywords: Ability, Reading, Exposition Text